Does representation of women in parliament promote economic growth? Considering evidence from Europe and Central Asia - Mirziyoyeva, Ziroat; Salahodjaev, Raufhon (Frontiers in Political Science, 2023)
This study aims to investigate the relationship between female empowerment in public service and economic growth in Europe and Central Asia. This study uses panel data from 2000 to 2018 and applied panel fixed and random effects regression and a two-step system GMM estimator to assess the impact of the proportion of national parliament seats held by women on GDP growth. The empirical results suggest that female participation in parliament has a positive and significant effect on economic progress. In particular, a 10%-point increase in women’s representation in parliament leads to a 0.74%-point increase in GDP growth. Thus, it is essential to further promote female empowerment programmes in developing countries and continue to adopt new measures aimed at increasing the participation of women in public service.